The Effect of Health Service Standard And Service Quality To Patient Satisfaction Of Bpjs Users in The Internal Disease Policlinic In Rsud Prambanan Yogyakarta - Wachid Nur Hidayat (Jurnal Admmirasi, 2019)
Improving health care standards can not be separated from customer satisfaction as a service user. Quality of hospital services is an important element in health care services. Hospitals are required to provide the best quality services, to become health service providers who play an active role and also support the goal of health development in the National Health System (SKN). To analyze the effect of health service standard and service quality on patient satisfaction of BPJS users in the Internal Disease Policlinic of Prambanan Hospital. This research was descriptive quantitative with a cross-sectional approach. The population used in this research was patients of BPJS participants who checked in Internal Disease Polyclinic of Prambanan Hospital namely 10,573 people. The sample of this research was 100 people with the sampling techniques used purposive sampling. Data analysis used regression analysis. The health service standard has a positive and significant effect on patient satisfaction. Service Quality has a positive and significant impact on patient satisfaction. Health service standards and service quality have a positive and significant influence on the patient satisfaction of BPJS users in the Internal Disease policlinic of Prambanan Hospital. The amount of contribution of the health service standard and the service quality is 60,8% while 39,2% is influenced by other factors not examined in this research. The conclusion are health service standard and service quality have a positive and significant influence on the patient satisfaction of BPJS users in the Internal Disease Polyclinic of Prambanan Hospital with the contribution of 60,8%.